(untitled) (Research, Society and Development, 2024)
This integrative review seeks to evaluate the effectiveness of the use of platelet-rich plasma in preventing infections after cardiovascular surgeries through the analysis and comparison of existing studies in the database, given that sternal infections are common complications in cardiac surgeries and the search for its prevention is of high importance in medical care. Articles were searched using the descriptors: Surgical wound infection and Platelet-rich plasma, on the platforms: PubMed, Scielo, and BVS. The inclusion criteria used were: articles related to the area of ​​cardiovascular surgery with the use of PRP, published in the last 10 years and written in Portuguese or English. 7 articles were selected and later analyzed according to their degree of recommendation and level of evidence. The study concluded that the use of PRP is effective in reducing post-surgical complications and improving wound healing, however, the lack of studies in the area makes it necessary to carry out more high-quality studies.